2015
DOI: 10.1007/s11357-015-9783-z
|View full text |Cite
|
Sign up to set email alerts
|

Environmental heat exposure and cognitive performance in older adults: a controlled trial

Abstract: Thermal stress has a negative effect on the cognitive performance of military personnel and industry workers exposed to extreme environments. However, no studies have investigated the effects of environmental thermal stress on the cognitive functions of older adults. We carried out a controlled trial with 68 healthy older adults (mean age 73.3 years, 69 % female), each of whom has been assessed twice on the same day with selected tests from the Cambridge Neuropsychological Test Automated Battery (CANTAB). Repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 35 publications
2
11
2
3
Order By: Relevance
“…We are not able to provide the answer to why RH affects performance. However, the results are consistent with the work of Trezza et al [69] who showed that exposure to relative humidity higher than 57.8% reduces cognitive performance.…”
Section: Results Of the Frontal Lobe Temporal Lobe And Occipital Lobesupporting
confidence: 92%
“…We are not able to provide the answer to why RH affects performance. However, the results are consistent with the work of Trezza et al [69] who showed that exposure to relative humidity higher than 57.8% reduces cognitive performance.…”
Section: Results Of the Frontal Lobe Temporal Lobe And Occipital Lobesupporting
confidence: 92%
“…O crescimento do envelhecimento populacional, principalmente em cidade de médio e pequeno porte (Hoof and Hensen, 2006;Iommi and Barbera, 2015;Lai et al, 2014;Larose et al, 2014;Organização Mundial da Saúde, 2015;Schellen et al, 2010;Trezza et al, 2015), bem como o aumento da porcentagem de pessoas obesas em todo o planeta (Okada and Kakehashi, 2014;Vanos et al, 2012;WHO, 2017), fazem parte de um padrão crescente do novo modelo de crescimento populacional urbano.…”
Section: Introductionunclassified
“…The thermal stress can cause health effects on the population of São Paulo, such as respiratory morbidity (Gonçalves et al, 2005). The thermal discomfort will increase in São Paulo due to climate changes (Batista et al, 2016) and the elderly can suffer with heat discomfort indoors (Alves, Duarte and Gonçalves, 2016) and cognitive problems (Trezza et al, 2015).…”
Section: Chemical Composition Of Pmmentioning
confidence: 99%